OnabotulinumtoxinA infiltration and nerve blocks in patients with headache and neuralgia: safety recommendations to prevent SARS-CoV-2 infection - Santos-Lasaosa, S.; Porta-Etessam, J. (Neurología (Barcelona, English ed. ), 2020)
The COVID-19 pandemic has given rise to the need for changes in clinical practice, with new strategies to enable integrated care for patients with headache and neuralgia. Given the high spreadability of SARS-CoV-2, new safety measures are required in such procedures as onabotulinumtoxinA infiltration and nerve blocks. We present a series of recommendations based on the measures implemented to prevent infection in our healthcare system. We differentiate between measures related to patients and physicians, to technique, to infrastructure (waiting room and consultation), and to healthcare management. La infección por SARS-CoV-2 y la situación de pandemia hacen necesario un cambio en nuestra práctica clínica, en relación con la adopción de nuevas estrategias que permitan la asistencia integral de los pacientes con cefalea y neuralgia. Ante la elevada capacidad de transmisión del virus, determinados procedimientos, como la infiltración de onabotulinumtoxinA y la realización de bloqueos anestésicos, deben realizarse adoptando medidas que garanticen un nivel adecuado de seguridad. Nuestro objetivo es presentar una serie de recomendaciones basadas en las medidas establecidas por nuestro sistema sanitario para evitar el contagio. Diferenciaremos entre aquellas medidas relacionadas con el paciente y el facultativo, con la técnica, con la infraestructura (sala de espera y consulta) y con la gestión asistencial.